The influence of acetabular morphology on prediction of proximal femur fractures types in an elderly population - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2017)
Introduction: The role of proximal femur morphology to the development of certain proximal femur fracture types both femoral neck and trochanteric fractures has been observed. However, the relavance of acetabular morphology to the development of proximal femur fractures is not extensively questioned. Therefore the aim of the study was to determine whether there is a correlation between acetabular morphology and pathogenesis of 2 different hip fracture types after low energy trauma. Methods: This retrospective study includes 60 cases (41 women, 19 men) with a proximal femoral fracture after a low energy trauma between July 2012 and December 2014. Acetabular depth and acetabular index were measured on pelvic radiographs. Neck shaft angle, hip axis length and cortical index were measured on pelvic computed tomography scans. All measurements were performed on the contralateral hip. Results: Mean age was 77.56 +/- 8.99 years (range 61-92 years). No statistically significant difference was found with regard to neck shaft angle, acetabular depth or cortical index measurements between patients with femoral neck fracture and patients with trochanteric femoral fractures (p> 0.05). Acetabular index measurement was higher (p = 0.001) and hip axis length measurement was lower (p = 0.001) in trochanteric fracture group as compared to femoral neck fracture. Conclusions: The rate of trochanteric femur fractures is higher in patients with high acetabular index, whereas the rate of femoral neck fractures is higher in patients with increased hip axis length.
Keywords: Acetabular index; Hip axis length; Neck shaft angle; Proximal femoral fracture; Proximal femur morphology; FEMORAL-NECK FRACTURES; HIP FRACTURE; TROCHANTERIC FRACTURES; GEOMETRY; RISK; OSTEOARTHRITIS; DYSPLASIA